Can adolescents' subjective wellbeing facilitate their pro-environmental consumption behaviors? Empirical study based on 15-year-old students - Zhang, Min; Zhang, Weidong; Shi, Yong (Frontiers in Public Health, 2023)
Purpose: To address the challenge of declining pro-environmental behaviors in adolescence, this paper uses the theoretical foundations for subjective well-being to verify the influence of three latent dimensions of subjective well-being (life satisfaction, positive emotions, and negative emotions) on adolescents' pro-environmental consumption behaviors (PECBs). Furthermore, we explore the moderating effects of nations and regions in the relationship between subjective well-being and PECBs in adolescents. Method: Based on the international data from the Programme for International Student Assessment 2018 (PISA 2018), we construct a unique dataset that includes 57,182 samples related to the subjective well-being and PECBs of 15-year-old students from eight countries/economies. Specially, we employ an ordered probit model to test our hypotheses. Findings: Both adolescents' life satisfaction and positive emotions can significantly improve their PECBs, while there is a significant negative association between negative emotions and PECBs. At the nation's level, adolescents' life satisfaction and negative emotions in developed countries/economies significantly impact PECBs. In contrast, the positive emotions of adolescents in developing countries/economies have more substantial effects on PECBs. At the regional level, the impact of all three dimensions of adolescents' subjective well-being on PECBs is more significant in rural than urban areas. Originality/value: This paper provides a new perspective for understanding adolescents' PECBs from the insights of subjective well-being. Previous studies have examined the effects of life satisfaction or happiness on PECBs in adults. This paper examines the impact of subjective well-being on adolescents' PECBs from life satisfaction, positive emotions, and negative emotions, which suggests that promoting adolescents' subjective well-being can be an effective strategy for encouraging PECBs. From a comparative research perspective, we further analyze the differences between the nations at different levels of development, the rural and urban areas, providing a valuable reference for policymakers and practitioners in promoting pro-environmental behaviors among adolescents.